Atypical initial presentations of Sjogren’s syndrome: a case series - Faiza Naeem; Imami, Salman Khurshid; Saira Elaine Anwer Khan; Shabnam Batool; Muhammad Akmal; Yasir Mushtaq (Journal of the Pakistan Medical Association, 2024)
Primary Sjogren’s syndrome (pSS) typically presents with Sicca symptoms xerostomia and xeropthalmia. This study highlights atypical presentations of Primary Sjogren’s syndrome posing diagnostic and therapeutic challenges. Four female patients (median age 30 years, IQR = 15.5) with atypical pSS features, confirmed by positive Anti-Ro antibodies and negative lupus or rheumatoid arthritis tests, were treated between February and August 2023. PSS presented as erythema nodosum, soft tissue swelling with medium-vessel vasculitis, palpable purpura, and severe thrombocytopenia in these cases prior to Sicca symptoms. Initial treatment included steroids and hydroxychloroquine. Azathioprine, Methotrexate, and Cyclophosphamide were added as steroid-sparing agents. Three patients achieved remission. One patient with co-existing pulmonary tuberculosis (TB) died. Atypical features can occur in SS, requiring vigilance for diagnosis and individualised treatment. Our series demonstrates the diverse atypical clinical features of Sjogren’s syndrome, encompassing radiologic, histopathologic, laboratory abnormalities, and treatment guidelines, expanding the known spectrum of disease presentation and management. Keywords: Primary Sjogren’s syndrome, Takayasu arteritis, Medium vessel vasculitis, Palpable purpura, Thrombocytopenia.